PERKEMBANGAN PSIKOLOGI PESERTA DIDIK DI TINGKAT MI/SD - Harahap, Asriana; Suhendra, Ade; Sumarni, Sri; Saadah, Nurus (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2025)
AbstractThe psychological development of students in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) is a very important aspect in forming the foundation of children's education. Elementary school is a very crucial period in the psychological development of children, where children not only experience cognitive growth, but also social, emotional, and behavioral development that will affect their learning process throughout life. This study aims to understand the psychological development of students in Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) and the factors that influence it. This study uses a qualitative approach with a case study design on a number of students in several MI and SD. The results of the study indicate that the psychological development of students is influenced by internal and external factors, including age, family environment, and social interactions at school. These findings provide insight into the importance of a psychological approach in basic education to support optimal child development. Keywords: Student Psychology, Psychological Development, MI/SD.